2nd PSL Chemical Biology Symposium (2019): At the Crossroads of Chemistry and Biology. (25th February 2019) - Lucchino, Marco; Billet, Anne; Versini, Antoine; Bavireddi, Harikrishna; Dasari, Bhanu‐Das; Debieu, Sylvain; Colombeau, Ludovic; Cañeque, Tatiana; Wagner, Alain; Masson, Géraldine; Taran, Frédéric; Karoyan, Philippe; et al.
Abstract: Chemical Biology is the science of designing chemical tools to dissect and manipulate biology at different scales. It provides the fertile ground from which to address important problems of our society, such as human health and environment. Abstract : For the 2nd PSL Chemical Biology Symposium, the state of the art in chemical biology has been presented by world leaders to feature the latest innovation and future perspectives in this dynamic and innovative field.